Girls in power : gender, body, and menstruation in adolescence - Fingerson, Laura, 1974- (Albany : State University of New York Press, 2006)
"Girls in Power offers a look at the social aspects of menstruation in the lives of adolescent girls - and also in the lives of adolescent boys. The book extends our theoretical and analytical understanding of youth, gender, power, and embodiment by providing a more balanced view of adolescent social life."--Jacket.
Negative and Ambivalent Experiences -- Cultural Contexts -- Medicalization and Gender Politics of the Body -- Girls in Power -- Boys' Responses -- Conclusion: Bodies in Interaction.
Includes bibliographical references (pages 177-185) and index.
Print version record.
JSTOR
Keywords: Teenage girls -- Psychology; Menstruation -- Social aspects; Human body -- Social aspects; Sex role; Adolescentes -- Psychologie; Menstruation -- Aspect social; Corps humain -- Aspect social; Rôle selon le sexe; sex role; FAMILY & RELATIONSHIPS -- Life Stages -- Adolescence; FAMILY & RELATIONSHIPS -- Life Stages -- Teenagers; Human body -- Social aspects; Menstruation -- Social aspects; Sex role; Teenage girls -- Psychology